Defining Britishness/otherness on the example of freak shows in the 19th century - Sosnowska, Monika (The British Empire: Interdisciplinary Deliberations, 2019)
The article focuses on the social contruction of Britishness and otherness on the example of British cultural practices known as freak shows – exhibitions of abnormal corporeality. They were popular entertainment of the late 1800s and early 1900s, especially in British but also in American culture. Somatic anomality became not only a social stigma meaning monstroity and oddity but it was also a defining category of non-Britishness and non-humanness. The author accentuates the significance of the sense of vision in fabricating and naming physical Otherness as negativity and deformity. The article demonstrates that the exhibition of extraordinary bodies within their particular historical, cultural and political context served a purpose to normalize sameness and establish identity of British middle and upper class of the discussed period. British colonizers represented the colonized in general as Others, yet another „othering” aspect of the Other was an exposition of their somatic freakishness, something that aroused fear and fascination. Bizarre bodies of the Others became additional territory to be subjugated and marked by means of exclusion and degradation.